Women's International League for Peace and Freedom Peace Conference with Dr. David Wright at Fresno Pacific College - Watkins, Howard::::::::: (1989)
Dr. David Wright speaking at lectern Women's International League for Peace and Freedom Peace Conference with Dr. David Wright at Fresno Pacific College